Estimativas da radiação difusa horária incidente em superfícies inclinadas com base na transmissividade atmosférica - Souza, Adilson Pacheco de; Escobedo, João Francisco [UNESP]; Pai, Alexandre Dal; Gomes, Eduardo Nardini [UNESP] (My University, 2012)
Evaluated statistical equations estimates (based on radiometric fractions) of the hourly diffuse radiation incident on inclined surfaces for the North to 12.85, 22.85 and 32.85°, the climate and geographical conditions of Botucatu, SP. The database was generated from April/1998 to December/2007, with measures in the three tilted surfaces in different periods, but concomitant to the horizontal plane. In the validation of the equations were used indicative statistics MBE (mean absolute error), RMSE (square root mean square error) and index adjustment (d) for three inclinations and conditions of sky coverage. The increased angle of inclination of the surface led to increased scattering of hourly values for the coefficient of atmospheric transmissivity of diffuse radiation for inclined and horizontal surfaces. Estimates of diffuse radiation on the basis of hourly tilted horizontal global radiation occur for quadratic polynomial models, which adjust K'Dβ maximum values of between 0.14 and 0.30 for winter and summer when KTH varies between 0.40 and 0.66, indicating that energy, the highest values of diffuse radiation occur in partly cloudy sky conditions and / or partially open. The increase in atmospheric transmissivity decreases the performance of annual and monthly equations at all inclinations.

Foram avaliadas equações estatísticas de estimativas (com base em frações radiométricas) da radiação difusa horária incidente em superfícies inclinadas para o Norte a 12,85, 22,85 e 32,85º, nas condições climáticas e geográficas de Botucatu, SP. A base de dados foi gerada entre abril/1998 a dezembro/2007, com medidas nas três inclinações em diferentes períodos, todavia concomitantes ao plano horizontal. Na validação das equações, foram empregados os indicativos estatísticos MBE (erro absoluto médio), RMSE (raiz quadrada do quadrado médio do erro) e índice de ajustamento (d), para as três inclinações e em diferentes condições de cobertura de céu. O aumento do ângulo de inclinação da superfície propiciou aumento do espalhamento dos valores horários para o coeficiente de transmissividade atmosférica da radiação difusa para superfícies inclinada e horizontal. As estimativas da radiação difusa horária inclinada com base na radiação global horizontal ocorrem por modelos polinomiais quadráticos, que ajustam valores máximos de K’Dβ entre 0,14 e 0,30 para inverno e verão quando KTH varia entre 0,40 e 0,66, indicando que energeticamente, os maiores valores de radiação difusa ocorrem em condições de céu parcialmente nublado e/ou parcialmente aberto. O aumento da transmissividade atmosférica diminui o desempenho das equações anuais e mensais em todas as inclinações.
Estimates of hourly diffuse radiation incident on tilted surfaces based on atmospheric transmissivity
Keywords: Solar radiation; Radiometric fractions; Statistical index; Radiação solar; Frações radiométricas; Indicativos estatísticos